Nurturing Students’ Critical Thinking Skills by Using Social Media Based on E-Portfolio - Silvana, Rini (JET ADI BUANA, 2016)
Integrating critical thinking and problem solving in dailyclassroom activities is vital for students as learning critical thinkingleads students to develop other skills, such as a higher level ofconcentration, deeper analytical abilities, and improved thoughtprocessing. Meanwhile, portfolio is part of an alternative assessmentneeded in assessing both learning process and learning product. Itcan either include a record of students’ achievement or simplydocument their best work (Nunes, 2004: 327). Integration oftechnology and education has made traditional paper-basedportfolios turn to digital portfolios which are much more userfriendly and appealing to students, particularly those who areattracted to use social media in their daily lives. This paper aims tofind out how e-portfolio helps nurture students’ critical thinkingskills. To achieve the objective, an action research involvingplanning, acting, observing and reflecting is conducted in preintermediate English for teen class. In addition, students’ perceptionof using e-portfolio during their learning is also investigated.